Renaming schizophrenia: 5 × 5 - Guloksuz, Sinan (Epidemiol Psychiatr Sci, 2018)
There had been a long way to go before we felt comfortable about even discussing the issues revolving around the concept of ‘schizophrenia’, let alone reckoning on mere semantic revision. In this editorial, we aim to extend our discussion on the reasons behind the slow death of the concept of ‘schizophrenia’ and the benefits of changing the name and embracing a spectrum approach with an umbrella psychosis spectrum disorder (PSD) category (similar to autism spectrum disorder) that goes further than a mere semantic revision. We attempted to cover the topic of the renaming by providing five most pertinent points categorised under five domains: reasons, signals, challenges, promises and steps for the change. Admittedly, even a modest revision, such as classifying all psychotic disorder categories under an umbrella category of PSD, and abolishing the term schizophrenia requires careful deliberation and some effort in the beginning, but the revision is well worth the effort considering the benefits in the long run. Renaming a particular form of mental suffering should be accompanied by a broader debate of the entire diagnosis-evidence-based-practice (EBP)-symptom-reduction model as the normative factor driving the content and organisation of mental health services that may be detached from patients’ needs and reality, overlooks the trans-syndromal structure of mental difficulties, appraises the significance of the technical features over the relational and ritual components of care, and underestimates the lack of EBP group-to-individual generalisability. Individuals may make great strides in attaining well-being by accommodating to living with mental vulnerabilities through building resilience in the social and existential domains. Changing the name and the concept of ‘schizophrenia’, which goes beyond a mere semantic revision, may become the first step that allows catalysation of the process of modernising psychiatric science and services worldwide.